RNA-seq of macrophages of amoeboid or mesenchymal migratory phenotype due to specific structure of environment - Čermák, Vladimír (Sci Data, 2018)
M2-polarized macrophages have been shown to adapt their 3D migration mode to physical properties of surrounding extracellular matrix. They migrate in the integrin-mediated adhesion and proteolytic activity-dependent “mesenchymal” mode in stiff matrices and in the integrin and protease-independent “amoeboid” mode in low density, porous environments. To find out what impact the switching between the migration modes has on expression of both protein-coding and non-coding genes we employed RNA sequencing of total RNA depleted of ribosomal RNA isolated from macrophages migrating in either mode in 3D collagens. Differentially expressed genes from both categories have been detected and the changes in expression of selected genes were further validated with RT-qPCR. The acquired data will facilitate better understanding of how mechanical properties of tissue microenvironment reflect in macrophage immune function and how the transitions between mesenchymal and amoeboid migratory modes are regulated at the gene expression level.